Occurrence of equatorial plasma bubbles over Kolhapur - Sharma, A.K.; Nade, D.P.; Nikte, S.S.; Patil, P.T.; Ghodpage, R.N.; Vhatkar, R.S.; Rokade, M.V.; Gurubaran, S. (My University, 2014)
This paper reports the nightglow observations of OI 630.0 nm emissions, made by using all sky imager operating at low latitude station Kolhapur (16.8°N, 74.2°E and dip lat. 10.6°N) during high sunspot number years of 24th solar cycle. The images are analyzed to study the nocturnal, seasonal and solar activity dependence occurrence of plasma bubbles. We observed EPBs in images regularly during a limited period 19:30 to 02:30 LT and reach maximum probability of occurrence at 22:30 LT. The observation pattern of EPBs shows nearly no occurrence during the month of May and it maximizes during the period October–April. The equinox and solstice seasonal variations in the occurrence of plasma bubbles show nearly equal and large differences, respectively, between years of 2010–11 and 2011–12.
Keywords: Plasma bubbles; All sky imager; OI 630.0 nm images; Equinox; Solstice; Kolhapur